"Modélisation et diagnostic des défauts dans les moteurs asynchrones à cage d'écureuil : Détection de défaut du roulement" - إسحاق, غطاس; إسماعيل, حامدي; خالد, بن هنية (University of El-Oued, 2022)
"Electrical rotating machine have big importance in our daily life and especially in industries. Among these machines, we distinguish squirrel cage machine, which is the most used in the industry sector. According to these kind of machines can get damaged at any time. It can be because of huge losses as a result diagnostic process at early time became a necessity before the damages transform to a failure. Furthermore, in the field of diagnostic and surveillance of the damages there are a lot several methods to detect damages in the asynchronous machines (induction machines). Among these techniques, we mention :Motor Vibration Signature Analysis (MVSA) which are based on spectral analysis of vibration signals using Fourier Fast Transform (FFT). The aim of this work is to contribute to the detection, monitoring and diagnosis of faults in induction machine (IM) type. So, in this study we have tried to diagnose Rolling Element Bearing fault in asynchronous machine using the method Motor Vibration Signature Analysis in order to check the condition of the machine and its efficiency. In addition, and in order to find more information about the IM state, we used some statistical indicators as Kurtosis. " "الآلات الكهربائية الدوارة مهمة جدا في الحياة اليومية وذلك لتواجدها في العديد من المجالات ومن بين هذه الآلات نذكر الآلة غير المتزامنة ذات قفص السنجاب التي تعد واحدة من أكثر الآلات رواجا واستخداما في المجال الصناعي . هذه الأخيرة يمكن أن تتعرض لأي خلل في أي وقت ويسبب ذلك خسائر كبيرة، لذا فإن عملية تشخيص العيوب قبل أن تتحول إلى عطب في وقت مبكر أصبح أمرا ضروريا. علاوة على ذلك وفي مجال التشخيص ومراقبة العيوب يوجد العديد من الطرق للكشف عن العيوب في الآلات غير المتزامنة ومن بين هذه الطرق : طريقة تحليل الإشارة الاهتزازية التي تعتمد بالأساس على التحليل الطيفي بواسطة تحويلات فوريي. الهدف من هذا العمل هو المساهمة في الكشف، مراقبة وتشخيص العيوب التي تتعرض لها هذه الماكينة الكهربائية، لذا حاولنا في هذه الدراسة تشخيص عيب المحمل للآلة غير المتزامنة بطريقة تحليل الإشارة الاهتزازية من أجل التحقق من حالة الآلة وكفاءتها . كما قدمنا تحليل لمقادير إحصائية من شأنها تقديم مؤشرات حول الخلل و من بينهم التفلطح. "
مذكرات ماستر تخصص الات
Keywords: Electrical rotating machine, Motor Vibration Signature Analysis (MVSA), Asynchronous Machines, Spectral Analyzing, Fourier Fast Transform (FFT), Rolling Element Bearing, Kurtosis.; الآلات الكهربائية، الآلات غير المتزامنة، طريقة تحليل الإشارة الاهتزازية، المحمل، التحليل الطيفي، تحويلات فوريي، التفلطح.